(3QSGdI aj GdCVOGOs ((3YHO GdaJGM Hf MSf Hf eMehO Hf CMeO Hf MSf GdehUdi s)
(3ChdgG (B:s
(3CSHZ YdjfG fYeG dG JQje hHYO , adeG GTJedJ GdYQHjI Ydi cdeGJ , hVYJ ddOdGdI Ydi GdVOjf , hZad YfgG ef CZad JUaM GddZGJ GdJbJWgG MSH GdGSJWGYI ebOeI cGdLhf ddCHjV s
(3BNQgG (B:s
(3hJfGOhG GLJeYhG , hGdTF JaQb hQGAg Ndag , hbO jchf HeYfi bOGe , agh ef GdCVOGO Je hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3eQJHI Ydi MQha GdeYLes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs